PERAN UMKM GERABAH DALAM MENDUKUNG PEREKONOMIAN MASYARAKAT KAMPUNG KOSAMBI - Anah Hasanah; Ufus Indriani; Zahwa Aulianova; Ade Fauji (Nindikayla Institute, 2026)
This study aims to analyze the role of pottery craft micro, small, and medium enterprises (MSMEs) in supporting the community economy in Kampung Kosambi, Ciruas District. Pottery MSMEs were selected due to their high cultural and economic potential, yet they still face production and marketing challenges. The method used is qualitative descriptive with data collection through observation, interviews, and documentation. Results indicate that the pottery business absorbs more than 20 local workers, increases household income, and preserves traditional craftsmanship. However, constraints such as weather dependency during drying, cracking during firing, limited capital, and conventional marketing remain prominent. This study concludes that digital marketing strategies, product innovation, and institutional support are essential to sustainably enhance the productivity and economic impact of pottery MSMEs.